Mobility for the Exceptionals: An Adaptable Electrified Transportation System for Manual Wheelchair - Adharv R; Amarjith A.S; Rahul Raj; Rashin R; Vidya Surendran (International Journal of Robotics and Automation in Mechanics, 2024)
The survey for the prevalence of handicapped people in India reveals that approximately 4.52% of India’s total population is physically challenged. Among the list, about 44% of people suffer from locomotor disability. Satisfaction of their primary need will be fulfilled when they get aid to move but the main problem is that about 31% of India’s population belongs to middle class or lower middle class. Their wish to buy an electric wheelchair which costs more than 1 lakh will be hard to get and unaffordable but their wish to move is the motive of our project. Our project “mobility for the exceptional: an adaptable electrified transportation system for manual wheelchair” deals with a plug-and-play electrified locomotor system that can be adaptable to any manual wheelchair. The mechanical system allows motors to turn the rear wheels through friction without permanently modifying the original wheelchair and the controlling systems are also user friendly. This budget-friendly wheelchair system comes in a price range of less than 50000 and that is 50% less than the electric wheelchairs currently available in our market. The goal of the project is to enable people with wheelchairs to navigate outdoor uses and long distances that are not suitable for manual wheelchairs.
Keywords: BLDC Motor; ECU; Li-ion battery; MCU; Throttle